Social Beliefs as Determinants of Attitudes Toward Seeking Professional Psychological Help among Ethnically Diverse University Students - Kuo, Ben C. H.; Kwantes, Catherine T.; Towson, Shelagh; Nanson, Kathleen M. (Canadian Journal of Counselling and Psychotherapy, 2007)
English The present study examined the role of pancultural social beliefs, as measured by the Social Axioms Survey (SAS), in predicting attitudes toward seeking professional psychological help in an ethnically-diverse sample of Canadian university students (N=400). The result of a hierarchical regression showed that the collective contribution of the six SAS factors was significant in explaining help-seeking attitudes. Overall, gender, age, ethnicity, perceived stress, and two SAS factors (Social Cynicism and Interpersonal Harmony) emerged as the significant predictors of help-seeking attitudes. There were also gender and ethnic differences in help-seeking attitudes, perceived stress, and across the six SAS factors. FrançaisNon disponible